2011
DOI: 10.4028/www.scientific.net/amr.332-334.1816
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties Studies of Cellulose Super Absorbent Polymer

Abstract: In this paper, super absorbent polymer was prepared through graft copolymerization by cellulose and acrylic acid (AA), acrylamide (AM), and butyl methacrylate (BMA) and its properties were determined. It showed that optimum reaction condition is the amount of cellulose, AA, AM and BMA is 10g, 4.5g, 2g and 1.5g respectively, the amount of initiator (potassium persulfate) and N,N'-methylene bisacrylamide is 0.01g and 0.012g, the pH value of AA after neutralization is 7. The water absorbency to distilled water, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The synthesis of organic-inorganic composite water retaining agent is of great significance for the efficient development of natural mineral resources and the improvement of the utilization value of minerals. In addition, in recent years, many universities and research institutes have chosen to use some raw materials with wide sources and low prices to develop and prepare other new water retaining agent products with strong water absorption capacity, fast water absorption speed, long duration, low price, and wide application range, such as bamboo fiber grafted acrylate polymer water retaining agent [12], seaweed biological water retaining agent [13], modified cotton stalk cellulose salt resistant water retaining agent [14], apple pomace water retaining agent [15], and other new water retaining agents [16][17][18], which have the advantages of easy degradation, green environmental protection, and low cost.…”
Section: Categories Of Wramentioning
confidence: 99%
“…The synthesis of organic-inorganic composite water retaining agent is of great significance for the efficient development of natural mineral resources and the improvement of the utilization value of minerals. In addition, in recent years, many universities and research institutes have chosen to use some raw materials with wide sources and low prices to develop and prepare other new water retaining agent products with strong water absorption capacity, fast water absorption speed, long duration, low price, and wide application range, such as bamboo fiber grafted acrylate polymer water retaining agent [12], seaweed biological water retaining agent [13], modified cotton stalk cellulose salt resistant water retaining agent [14], apple pomace water retaining agent [15], and other new water retaining agents [16][17][18], which have the advantages of easy degradation, green environmental protection, and low cost.…”
Section: Categories Of Wramentioning
confidence: 99%
“…Most likely, water‐based polymerization techniques such as emulsion polymerization are the best choice as some monomers are not water soluble. Such a technique can also yield products with higher solid contents at lower viscosities, which is desirable from a polymer processing standpoint (Brock Thomas et al, 2006; Dettmer et al, 2009; Liu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In typical cases the latter value is less than half of the absorption capacity in the case of pure water. Especially sharp contrasts in capacity, when comparing deionized vs. saline water, have been reported in the case of superabsorbent hydrogels (Lim et al 2001;Suo et al 2007;Zhang et al 2008bZhang et al , 2009Kim and Mun 2009;Liang et al 2009;Pourjavadi et al 2008Pourjavadi et al , 2009Chang et al 2010;Bao et al 2011;Liu et al 2011;Wang et al 2011a,c,d;Wu et al 2012).…”
Section: Effects Of Salinitymentioning
confidence: 99%
“…Considerable research has been devoted to the development of copolymers in which CMC is reacted with acrylic monomers and various crosslinking agents to form SAPs (Kuwabara and Kubota 1996;Pourjavadi and Mahdavinia 2005;Pourjavadi and Ghasemzadeh 2006;Abd El-Mohdy 2007;Ibrahim et al 2007;Pourjavadi et al 2007aPourjavadi et al -b, 2008Pourjavadi et al , 2009Pourjavadi et al , 2010Suo et al 2007;Ali et al 2008;Chen et al 2008;Yang et al 2009;El-Din et al 2010;Feng et al 2010a;Lin et al 2010;Bao et al 2011;Eldin et al 2011;Huang et al 2011;Liu et al 2011;Shu et al 2011;Varaprasad et al 2011;Wang et al 2011c). Water absorbency values generally in the range of 40 to 1400 g/g have been reported in such studies, with the highest value reported by Pourjavadi et al (2008).…”
Section: Copolymers Of Cmc By Reaction With Monomersmentioning
confidence: 99%
See 1 more Smart Citation